Influence of Celebrity Endorsement, Electronic Word of Mouth, Perceived Quality on Purchase Decision of Scarlett Whitening Consumer: Case Study on Consumer Store in Semarang City - Sapna Putri Handayani; Taviyastuti; Irawan Malebra (Politeknik Negeri Semarang, 2024)
The aim of this research is to find out the influence of celebrity endorsement, ewom, perceived quality on the purchase decision of Scarlett Whitening consumers, a case study of store consumers in Semarang City. Purposive sampling was used to take a sample of 120 people. In research, questionnaires, literature studies, and interviews are used in data collection. Data were processed using descriptive analysis, research instrument testing, and multiple linear regression analysis. Next, hypothesis testing is carried out consisting of the t test, F test, and coefficient of determination test. The majority of respondents are women aged 21 to 25 years who are students with salaries < IDR 2,000,000. The results of descriptive analysis on the indicators of the variables celebrity endorsement, ewom, perceived quality have a high interpretation with a range of 85-120. Based on the test results, the data is said to be valid and reliable. The results of the multiple linear regression analysis produced the equation Y = 21.049 + 0.234X1 + 0.186X2 + 0.334X3 + e. The results of partial and simultaneous hypothesis testing have a significant effect on purchase decisions. The results of the coefficient of determination test resulted in celebrity endorsement, ewom, and perceived quality influencing purchase decisions by 80.9% with the remaining 19.1% being influenced by other factors not explained in the research. Tujuan dari riset ini ialah untuk mencari tahu pengaruh celebrity endorsement, ewom, perceived quality pada purchase decision konsumen Scarlett Whitening studi kasus pada konsumen store di Kota Semarang. Purposive sampling digunakan dalam pengambilan sampel sebanyak 120 orang. Dalam penelitian, kuesioner, studi pustaka, dan wawancara dipergunakan pada pengumpulan data. Data diolah dengan analisis deskriptif, uji instrumen penelitian, dan analisis regresi linear berganda. Selanjutnya dilaksanakan uji hipotesis terdiri dari uji t, uji F, dan uji koefisien determinasi. Mayoritas responden ialah perempuan berusia 21 sampai 25 tahun yang mana pelajar/mahasiswa memiliki gaji < Rp 2.000.000. Hasil analisis deskriptif pada indikator dari variabel celebrity endorsement, ewom, perceived quality mempunyai interpretasi tinggi dengan rentang 85-120. Berdasarkan hasil uji, data dikatakan valid dan reliabel. Analisis regresi linear berganda menghsilkan persamaan Y = 21,049 + 0,234X1 + 0,186X2 + 0,334X3 + e. Hasil dari uji hipotesis secara parsial dan simultan berpengaruh signifikan pada purchase decision. Hasil dari uji koefisien determinasi menghasilkan celebrity endorsement, ewom, dan perceived quality berpengaruh terhadap purchase decision sebesar 80,9% dengan sisa sebesar 19,1% dipengaruhi oleh faktor-faktor lain yang tidak dideskripsikan pada riset.